Konsepsi Tata Letak Candi Candi Muaro Takus - Ardiansyah; Fransiska F.A. W; Muti’ah Nabila. S (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2024)
The discovery of ruins of temple buildings were generally discovered by colonial peoples, both Dutch and British, in the 19th and 20th centuries, with the form almost no longer intact, making it very difficult to identify and guarantee the correctness of the architectural form after renovation. The restoration results carried out by archaeologists, especially at temples in Sumatra, are generally only limited to the foot of the temple or the foundations. However, the layout and orientation of the temple buildings are visible, providing a solid guide and basis for interpreting the layout and orientation of temples in Sumatra. In this research, researchers took the case of temples in Sumatra, including Bumiayu Temple, Muaro Jambi Temple, and Muaro Takus Temple. The research methods chosen were field studies and literature studies with a qualitative approach. An important discovery in this research is the configuration of the Muaro Takus Temple as a replica of the mountain cluster on Bukit Barisan to the west and southwest of the temple, whereas in the case of the Muaro Jambi site, the natah room or central courtyard. This study of spatial planning is very important because it is related to the zoning, orientation and grouping of buildings in temple clusters in Sumatra